Definition of minimal disease activity in psoriasis. (28th July 2020) - Carretero, G.; Carrascosa, J.M.; Puig, L.; Sánchez‐Carazo, J.L.; López‐Ferrer, A.; Cueva, P.; Soria, C.; Rivera, R.; Belinchón, I.; ,
Abstract: Objective: To generate an operational definition to adequately reflect the construct 'Minimal Disease Activity (MDA)' in psoriasis. Methods: A systematic review of domains included in clinical trials of psoriasis was presented to a panel of dermatologists and patients. Further domains were elicited by panel discussions. Domains (and instruments measuring these) were items of two consecutive Delphi rounds targeting dermatologists from the Psoriasis Group of the Spanish Academy of Dermatology and Venereology and patients from the Acción Psoriasis association. The instruments selected were used to generate 388 patient vignettes. The expert group then classified these vignettes as 'No MDA/MDA/Unclassifiable'. The items were further reduced by factorial analysis. Using the classification variable as gold standard, several operational constructions were tested in regression models and ROC curves and accuracy was evaluated with area under the curve (AUC). Results: The following domains were included: itching, scaling, erythema and visibility by 0–10 scales, extension by BSA, impact on quality of life by DLQI, special location and presence of arthritis as yes/no. The definition with the highest AUC and best balance between sensitivity and specificity was the one including no presence of arthritis plus at least three others below the upper limit of the 95% confidence interval (AUC, 0.897; sensitivity, 95.2%, specificity, 84.1%). Conclusion: This study provides, for the very first time, the construct of 'Minimal Disease Activity' in psoriasis as agreed by dermatologists and patients. MDA is defined as absence of active arthritis plus 3 out of 6: itching ≤ 1/10; scaling ≤ 2/10; redness ≤ 2/10; visibility ≤ 2/10; BSA ≤ 2; DLQI ≤ 2; and no lesions in special locations. By design, domains are representative of disease impact. This MDA definition may be used as a measure of adequate management and replace other subjective or restrictive tools.